Protection of constitutional values in the conditions of the Russian-Ukrainian war - Т. І. Gudz (Bulletin of Kharkiv National University of Internal Affairs)
The study is devoted to the analysis of the peculiarities of the protection of constitutional values in Ukraine in the conditions of the Russian-Ukrainian war. Its purpose is to develop proposals for improving the mechanisms for ensuring these values.